2020
DOI: 10.1097/coc.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Trastuzumab Emtansine (T-DM1) and Concurrent Radiotherapy for Residual Invasive HER2-positive Breast Cancer

Abstract: Objectives: The treatment of nonmetastatic HER2-positive breast cancer with residual invasive disease using concurrent Trastuzumab emtansine (T-DM1) and radiotherapy appears to be an effective option. Our aim was to evaluate the acute side effects of this treatment regime. Methods: Fourteen patients were treated between March 2019 and April 2020 concurrent T-DM1 and radiotherapy. Left ventricular ejection fraction was assessed at baseline, before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Treatment with eight doses of DM1 in a three-day assay, including 0.1, 0.5, 2, 10, 30, 60, 100, and 300 nM, reduced cell viability to 24.82%, 7.09%, 6.25%, 3.32%, 2.03%, 0.83%, 0.80%, and 0.72% for CH157-MN and 26.88%, 11.12%, 7.65%, 3.99%, 2.87%, 2.05%, 1.84%, and 1.37% for AC07 ( Figure 3 A). The calculated IC 50 value of DM1 was 0.31 nM for CH157-MN and 0.56 nM for AC07, which confirmed that DM1 is a highly potent cytotoxin without cancer or tumor cell selectivity [ 30 , 31 ]. Treatment with nine doses of ADC, including 0.5, 1, 2, 10, 25, 50, 100, 250, and 500 nM, decreased the final viability of CH157-MN to 95.70%, 96.48%, 96.30%, 41.26%, 18.90%, 11.80%, 10.35%, 7.96%, and 2.67% ( Figure 3 A) with an IC 50 of 7.41 nM.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Treatment with eight doses of DM1 in a three-day assay, including 0.1, 0.5, 2, 10, 30, 60, 100, and 300 nM, reduced cell viability to 24.82%, 7.09%, 6.25%, 3.32%, 2.03%, 0.83%, 0.80%, and 0.72% for CH157-MN and 26.88%, 11.12%, 7.65%, 3.99%, 2.87%, 2.05%, 1.84%, and 1.37% for AC07 ( Figure 3 A). The calculated IC 50 value of DM1 was 0.31 nM for CH157-MN and 0.56 nM for AC07, which confirmed that DM1 is a highly potent cytotoxin without cancer or tumor cell selectivity [ 30 , 31 ]. Treatment with nine doses of ADC, including 0.5, 1, 2, 10, 25, 50, 100, 250, and 500 nM, decreased the final viability of CH157-MN to 95.70%, 96.48%, 96.30%, 41.26%, 18.90%, 11.80%, 10.35%, 7.96%, and 2.67% ( Figure 3 A) with an IC 50 of 7.41 nM.…”
Section: Resultsmentioning
confidence: 83%
“…Antibody–drug conjugates (ADCs) have been developed to treat cancers or tumors [ 19 , 20 , 21 , 22 ] and have demonstrated promising clinical efficacy and minimal adverse effects [ 23 , 24 , 25 , 26 ]. For instance, the gemtuzumab ozogamicin (anti-CD33 mAb-N-acetyl gamma calicheamicin conjugate) [ 27 , 28 ] for acute myeloid leukemia treatment, traztuzumab deruxtecan (anti-HER2 mAb-topoisomerase I inhibitor) [ 29 ] and trastuzumab emtansine (anti-HER2 mAb-Mertansine DM1 conjugate) [ 30 , 31 ] for chemotherapy refractory or advanced HER2-positive breast cancer, brentuximab vedotin (anti-CD30 mAb-MMAE conjugate) [ 32 , 33 ] for relapsed Hodgkin lymphoma, and 131 I-Tositumomab (anti-CD20 mAb-Iodine 131) [ 34 ] and 90 Y-Ibritumomab tiuxetan (anti-CD20 mAb-Yttrium-90) [ 35 ] for non-Hodgkin lymphoma have been approved by the FDA and used in clinics. Compared to standard chemotherapies, ADCs can specifically target cancer cells, deliver highly cytotoxic payloads, and reduce adverse effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no in vivo study was currently published on this subject. Zolcsák et al have also recently reported in a retrospective study of 14 patients that TDM-1 concomitantly administered with locoregional RT was well supported, without high-grade cardiac toxicity [ 43 ]. Of course, these results were obtained using a small number of subjects, and a validation cohort would be necessary to confirm these results.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of existing data is when T-DM1 is combined with conventionally fractionated RT [129][130][131][132][133] . Sideeffects reported in this setting are minimal (radiation dermatitis, pneumonitis and cardiac toxicities) and safety has been reported when administrated with concurrent RT in a recent systemic review 134 .…”
Section: T-dm1mentioning
confidence: 99%